NAD(P)H and Flavin Autofluorescence Correlation with ATP in Rat Livers with Different Metabolic Steady‐State Conditions. (4th September 2017) - Croce, Anna C.; Ferrigno, Andrea; Di Pasqua, Laura G.; Berardo, Clarissa; Bottiroli, Giovanni; Vairetti, Mariapia
Abstract: The monitoring of NAD(P)H and flavin autofluorescence (AF) is at the basis of numerous investigations on energy metabolism. Nevertheless, the ability of these AF biomarkers to accurately represent the energy currency, ATP, is poorly explored. Here, we focused on the AF/ATP correlation in lean and fatty livers with different steady‐state metabolic conditions, achieved after organ isolation, preservation and recovery, in a likely dependence on both liver intrinsic metabolic features and externally induced perturbations. Within these eventual, various conditions, a significant correlation was detected between liver NAD(P)H and flavin AF, measured via fiber‐optic probe, and biochemical ATP data, strengthening AF as biomarker of energy metabolism in steady‐state conditions for wide‐ranging experimental and diagnostic applications. Abstract : The autofluorescence of NAD(P)H and flavins directly reflects the different levels of intratissue energy, achieved by lean and fatty liver models when recovering from previous isolation and external perturbations induced by different conditions of preservation.